Daily streamflow forecasting using simplified rule-based fuzzy logic system - Mohd Shafiek, Yaacob, Dr.; Hishamuddin, Jamaluddin; Sobri, Harun (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/